2010
DOI: 10.1080/10349120903537764
|View full text |Cite
|
Sign up to set email alerts
|

Training Staff to Measure the Engagement of Children with Disabilities in Inclusive Childcare Centres

Abstract: Practitioner use of the revised Individual Child Engagement Record -Revised (ICER-R) for observing children with disabilities in inclusive childcare is examined. Training in the use of the ICER-R, which includes both a momentary time sampling observation system and rating scales, was provided across two training phases with five to seven participants. Four of the five participants who completed both phases of the training achieved greater than 80% inter-observer agreement on the observation measure within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Engagement observations using ICER-R (Kishida et al, 2008) An advantage of the ICER-R in this current research was that it combined both quantitative data, through partial interval time sampling, and qualitative data, through recorded observations. Using the ICER-R, observers record the types of engagement children exhibit, who they are interacting with, and whether any physical prompts were involved, at 15-second intervals as outlined in Kishida and Kemp (2010). In this research, two researchers observed two separate six-session programs.…”
Section: Instruments and Data Analysismentioning
confidence: 99%
“…Engagement observations using ICER-R (Kishida et al, 2008) An advantage of the ICER-R in this current research was that it combined both quantitative data, through partial interval time sampling, and qualitative data, through recorded observations. Using the ICER-R, observers record the types of engagement children exhibit, who they are interacting with, and whether any physical prompts were involved, at 15-second intervals as outlined in Kishida and Kemp (2010). In this research, two researchers observed two separate six-session programs.…”
Section: Instruments and Data Analysismentioning
confidence: 99%